2014
DOI: 10.1051/0004-6361/201323198
|View full text |Cite
|
Sign up to set email alerts
|

On the fine structure of the Cepheid metallicity gradient in the Galactic thin disk

Abstract: We present homogeneous and accurate iron abundances for 42 Galactic Cepheids based on high resolution (R ∼ 38 000) high signal-to-noise ratio (S /N ≥ 100) optical spectra collected with UVES at VLT (128 spectra). The above abundances were complemented with high-quality iron abundances provided either by our group (86) or available in the literature. We were careful to derive a common metallicity scale and ended up with a sample of 450 Cepheids. We also estimated accurate individual distances for the entire sam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
262
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(298 citation statements)
references
References 139 publications
31
262
2
Order By: Relevance
“…As a result, the initial and the present-day gradient derived for the younger populations are very similar out to 12 kpc. This fairly explains the similarity in the radial gradients observed for the younger tracers such as OCs of age less than 2 Gyr ( Figure 4 and figure 5), field stars (Cheng et al 2012;Hayden et al 2014) and Cepheids (Luck & Lambert 2011;Genovali et al 2014) for Rgc < 12 kpc. The steep gradient of slope −0.058 dex kpc −1 for stars younger than 2 Gyr in the radial range 6−11 kpc and a shallow gradient of old stellar populations predicted after taking the radial migration into account is in fair agreement with our values of gradient measured for respective age groups.…”
Section: Comparison With Chemodynamical Modelssupporting
confidence: 72%
See 1 more Smart Citation
“…As a result, the initial and the present-day gradient derived for the younger populations are very similar out to 12 kpc. This fairly explains the similarity in the radial gradients observed for the younger tracers such as OCs of age less than 2 Gyr ( Figure 4 and figure 5), field stars (Cheng et al 2012;Hayden et al 2014) and Cepheids (Luck & Lambert 2011;Genovali et al 2014) for Rgc < 12 kpc. The steep gradient of slope −0.058 dex kpc −1 for stars younger than 2 Gyr in the radial range 6−11 kpc and a shallow gradient of old stellar populations predicted after taking the radial migration into account is in fair agreement with our values of gradient measured for respective age groups.…”
Section: Comparison With Chemodynamical Modelssupporting
confidence: 72%
“…It is especially puzzling that the flattening of the metallicity distribution of OCs at large radii is not shown by the Galactic field stars (Cheng et al 2012;Hayden et al 2014) including Cepheids (Luck & Lambert 2011;Genovali et al 2014) where field stars suggest a constant steep decline of metallicity out to Rgc of 18 kpc. Another fascinating result, in common for both the field stars and OCs at large radii, is the evidence for enhanced [α/Fe] ratios in the outer Galactic disc (Yong et al 2005;Bensby et al 2011;Luck & Lambert 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of the Galactic abundance gradients in the thin disc using classical Cepheids have reported increased dispersion in the outer disc (Yong et al 2006;Lemasle et al 2008;Luck & Lambert 2011;Genovali et al 2014); however, these findings are hampered by the possible contamination of the current samples by misclassified Type II Cepheids that are thick-disc members. Including unrecognized Type II Cepheids modifies the abundance patterns not only because they belong to another stellar population but also because their current distances are computed with period-luminosity relations that are only valid for classical Cepheids.…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, there are some intriguing young objects in the MW that might be related to the same phenomenon: a) the puzzling low-metallicity supergiants located near the end of the Galactic bar (Davies et al 2009a,b, see discussion in Genovali et al 2014 andOriglia et al 2013); b) the young [α/Fe]-enchanced stars reported by Cunha et al (2007) near the Galactic Centre, and; c) the unusual Cepheid BC Aql which, despite being young (Whitelock, priv. comm.)…”
Section: What Is Their Origin?mentioning
confidence: 96%